Fruit processing by-products in the aquafeed industry: A feasible strategy for aquaculture sustainability - Mahmoud A. O. Dawood; Ola A. E. Habotta; Mabrouk Elsabagh; Mohamad Nor Azra; Hien Van Doan; Zulhisyam Abdul Kari; Hani Sewilam (John Wiley & Sons Australia, Ltd, 2025)
The aquaculture sector is steadily growing due to the increasing demand for healthy and cheap animal protein sources. Consequently, the high demand for nutritionally balanced aquafeed increases, but requires sustainable and feasible feed ingredients. However, the high cost of fish and soybean meals opens the door to looking for suitable non-traditional feed ingredients. The processing of fruits results in high amounts of waste and by-products, which are risky for the environment but rich in nutritional value. Recycling fruit waste in aquafeed is successfully applied and results in high growth performance, productivity and well-being of aquatic animals. Fruit byproducts are also potential functional feed additives devoted to their high content of polyphenols, flavonoids, vitamins, minerals, polysaccharides and peptides. As functional components, fruit by-products enhance the antioxidative and immune responses of aquatic animals and increase their tolerance for biotic and abiotic stressors. In light of reducing antimicrobial chemicals in aquaculture to mitigate antimicrobial resistance, dietary feed additives extracted from fruit by-products can be used as eco-friendly substances. The investigations involved in evaluating the incorporation of fruit by-products and their derivatives in aquafeeds are explored in this review. An overview of the possibility of using non-traditional plant products in aquaculture as a feasible and sustainable concept is addressed in this review. Academic knowledge with enough information for more development and research to maximise the utilisation of fruit by-products in the aquafeed industry is also enriched.